Abusive Supervision Scale Development in Indonesia - Wulani, Fenika; Purwanto, Bernadinus M; Handoko, Hani (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2014)
The purpose of this study was to develop a scale of abusive supervision in Indonesia. The study was conducted with a different context and scale development method from Tepperâs (2000) abusive supervision scale. The abusive supervision scale from Tepper (2000) was developed in the U.S., which has a cultural orientation of low power distance. The current study was conducted in Indonesia, which has a high power distance. This study used interview procedures to obtain information about supervisorâs abusive behavior, and it was also assessed by experts. The results of this study indicated that abusive supervision was a 3-dimensional construct. There were anger-active abuse (6 items), humiliation-active abuse (4 items), and passive abuse (15 items). These scales have internal reliabilities of 0.947, 0.922, and 0.845, in sequence.Â Â Â Â Â Â Â Â